Android Application of Traffic Density Visualization Based on Vehicle Speed - Setiawan, Widyadi; Budiastra, I Nyoman; Asri, Sri Andriati (Journal of Electrical, Electronics and Informatics; Vol 1 No 1 (2017): JEEI (February 2017), 2017)
This paper presents a system to display traffic density in real time based on speed of vehicles on the main roads in the city of Denpasar. With this application, users who are in a vehicle can get the density of roads information. The software will run on the Android platform created with the help of Google maps with visualization density of roads are being reviewed. Measurement of vehicle speed using the frame difference method, so the computational process can be run quickly and in real time. The trial results of this paper, user (vehicle speed measurement) produces the same data as the data is received by the client (viewer visualization) with the display format is the name of the location, vehicle speed, date and time data retrieval.